Policies and Strategies for Increasing Revenue Region Sector Through Tax - Rya Rizqi Amalia; Lathifah Hanim (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
The problem of this research is what strategies do for Boosting Regional Income Tax By Sector as well as what are the constraints and solutions in practice the tax collection. The method used in this study is a sociological juridical approach, in this case the authors emphasize research aimed at obtaining legal knowledge empirically by going directly to the field to see the condition of the actual tax collection practices.Based on the results of this study concluded that to streamline the management of taxes, some of the steps taken, among others, in addition to institutional changes also include improvements in the quality of human resources, with more technical personnel engage in structural and functional training. Meanwhile provided at taxpayer administer tax (especially payment) then checkouts cultivated close as possible to the location of taxes. Measures that have been done partly by making payments at BRI every district office, or can be deposited directly to the official tax collector. Obstacles encountered include the tax system is not maximized and necessary repairs, because it is still limited to the tax are estimated to have less control levels, whereas other tax sector is still using the old system (eg street lighting tax). The advice can be given in this study included the need for rigor in the implementation of tax legislation, this condition is manifested in the existence of a compromise in the tax collection system. In addition to the limited human resources, it is necessary to find a way out as soon as possible, whether fixed using existing human resources, cooperation with third parties in collecting taxes or empowering the village and district level personnel during the tax collection, especially for taxes routine. HR management is urgently needed, because given that if the tax levy can be optimally then tax receipts will always increase every year which will impact on the development of a local maximum.Keywords: Taxes; Autonomous Region; Local Revenue.